Coinfection by Aspergillus and Zygomycetes Species in a Case of Acute Rhinosinusitis - Vaidya, Dhara; Shah, Parul (Case Reports in Otolaryngology, 2011)
Invasive mycotic infections can be effectively treated if rapid identification of fungus is obtained. We reported a case of coinfection by Aspergillus and Rhizopus sp. involving nose, paranasal sinuses, orbit, and brain in a 68-year-old known hypertensive male. He was presented to ENT OPD with history of fever and intermittent headache since fifteen days along with history of right-sided nasal obstruction and proptosis since seven days. CT scan of brain and paranasal sinuses showed findings of pansinusitis with cellulitic changes in right orbit. MRI confirmed the same along with features of intracranial extension with focal meningitis in right frontotemporal region. Laboratory parameters did not conclude much except for leucocytosis and hyponatremia. Patient was taken for endoscopic debridement from nose and paranasal sinuses, and tissue was sent for microbiological and histopathological examination. Minced tissue was processed, and after 48 hrs of incubation two types of growth were identified, one was yellowish, granular, and powdery consistent with Aspergillus sp., and another was cottony and woolly consistent with Rhizopus sp. LCB mount confirmed presence of Aspergillus flavus and Rhizopus arrhizus. Patient responded to therapy with IV amphotericin B and surgical debridement. On discharge patient's condition was good.